#TITLE_ALTERNATIVE# - HADYAN KUSUMAWIJAYA (NIM : 101 07 067); Pembimbing Tugas Akhir : Dr. Novriana Sumarti, IQBAL
Activity on pre-disaster phase is closely related to the term disaster mitigation is an eÃ‚Â¤ort to minimize the impact caused by the disaster. Satellite mission is an eÃ‚Â¤ort of disaster mitigation. Satellites can be used to obtain spatial and environmental information, weather and climate, navigation of ships, transportation, education, and so on. Information obtained from satellite missions are expected to in‡uence decisions in favor of development. Only, the manufacture of the satellite mission has a very high price and uncertainty of bene…ts to be achieved. Bene…ts achieved can be said to be bene…cial, but diÃ‚Â¢ cult to estimate the amount. We will use the real options approach to optimize the time of the launch of a satellite mission. Beside that, we will see how the application of real option to launch the satellite in the European countries and Indonesia. The data obtained will be data-data from the economic losses and losses that can be saved from natural disasters. Losses from natural disasters is assumed to follow geometric Brownian motion. After that will be built a model of real options through the Contingent Claims Analysis to obtain an optimal time to launch a satellite mission. Especially for data loss disasters in Indonesia, the actual data will be merged with data simulated via Monte Carlo simulations. Investment such as satellite missions require a very large cost. Until now, Indonesia still using other state-owned satellite access to obtain information about disaster mitigation.